PURWARUPA SISTEM IDENTIFIKASI NYAMUK BERDASARKAN CITRA MIKROSKOPIS DIGITAL - Izzati Muhimmah; Novyan Lusiyana; Rizky Eka Listanto; Ratri Agung Nugraheni (Teknoin, 2016)
The modeling of the proposed mosquito identification system is one of the efforts to support the efforts of the Indonesian people in handling zoonotic cases. The incidence of deaths caused by a disease that is naturally transmitted between animals and humans is still quite high. This group of zoonotic diseases include dengue hemorrhagic fever, leptospirosis, cikunguya, and so forth. In the stages of diagnosis, it is necessary to read and identify the type of vector that causes zoonotic disease through microscopic observation. This process is often not done because in this laboratory examination service is not available evenly at the clinic level. In addition, with various types of vectors that the number of variations is very much, needed a way to be able to recognize the vector easily and quickly. Therefore, the prototype of this mosquito identification system needs to be developed. The data used to test system modeling consists of digital microscopic images of mosquito preparations taken from the Parasitology Laboratory of the Faculty of Medicine, Islamic University of Indonesia. Lecturer coordinator of this Parasitology lab will serve as a resource in determining the characteristics of vector and also as a provider of ground truth in the testing phase of the system.